Myopic loss aversion and stock investments: An empirical study of private investors - Lee, Boram; Veld-Merkoulova, Yulia (Journal of Banking & Finance, 2016)
Myopic loss aversion was suggested by Benartzi and Thaler (1995) as an explanation for the equity premium puzzle. Its main prediction is that loss averse investors, who evaluate their investment performance too frequently and therefore often observe small losses on their stock portfolios, would invest too little in equity. We investigate the link between myopic loss aversion and actual investment decisions of individual investors, using survey data. Our results are consistent with the predictions of Benartzi and Thaler. Higher myopic loss aversion is associated with lower stock investment as a share of total assets. Investors tend to evaluate their stock portfolio performance too often, which contributes to the prevalence of myopic loss aversion. The effect of myopia is most apparent when investors both evaluate their portfolios frequently and trade stocks regularly.